1,1'-{[1,4-Phenyl-enebis(methyl-ene)]bis-(-oxy)bis-(3,1-phenyl-ene)}diethanone - Al-Mohammed, N.N.; Alias, Y.; Abdullah, Z.; Khaledi, H. (Medknow Publications, 2011)
In the title compound, C(24)H(22)O(4), the centroid of the central benzene ring lies on a special position of 2/m site symmetry, while the terminal aromatic rings are located on a mirror plane. The central and terminal benzene rings are perpendic-ular to each other. In the crystal, the mol-ecules are connected via C-H⋯O hydrogen bonds into a three-dimensional polymeric structure. The network is further consolidated by a C-H⋯π inter-action.